DIGITALISASI AKTA NOTARIS SEBAGAI TANTANGAN DAN PELUANG DALAM MENJAGA KEUTUHAN DOKUMEN HUKUM - Zulfikar, Zulfikar (Lex Lectio Law Journal, 2024)
AbstractThe digitalization of notarial deeds is a modern solution to enhance the efficiency, security, and integrity of legal documents. While it offers numerous benefits, such as ease of access and cost reduction, its implementation faces challenges in regulation, data security, and standardization. The objectives include modernizing the notarial system, improving transparency, and supporting environmental sustainability. The success of digitalization relies on the development of clear regulations, reliable technological infrastructure, and the enhancement of human resource competencies.This study adopts a normative legal research method through literature review, analyzing primary, secondary, and tertiary legal sources related to the digitalization of notarial deeds. Descriptive-analytical qualitative analysis is applied, including legal interpretation and international comparisons. The findings are expected to contribute to the development of policies for the digitalization of notarial deeds in Indonesia. The digitalization of notarial deeds is crucial for modernizing Indonesia's notarial system, but regulatory gaps remain in the specific governance of digital deeds. The Notary Law does not explicitly accommodate digital notarial deeds, creating legal uncertainty. Key challenges include the validity of digital documents, data security, standardization of formats, and long-term storage. Human resources need to be equipped with technological skills, and collaboration among the government, notarial associations, and the private sector is essential for success. Digitalization offers improvements in efficiency, security, and transparency in notarial practices. It is vital for modernizing the notarial system in Indonesia, despite existing regulatory gaps, legal challenges, and infrastructure needs.AbstrakDigitalisasi akta notaris merupakan solusi modern untuk meningkatkan efisiensi, keamanan, dan integritas dokumen hukum. Meskipun menawarkan berbagai manfaat seperti kemudahan akses dan pengurangan biaya, implementasinya menghadapi tantangan peraturan, keamanan data, dan standarisasi. Tujuannya termasuk memodernisasi sistem notaris, meningkatkan transparansi, dan mendukung pelestarian lingkungan. Keberhasilan digitalisasi bergantung pada pengembangan regulasi yang jelas, infrastruktur teknologi yang andal, dan peningkatan kompetensi sumber daya manusia. Penelitian ini menggunakan metode hukum normatif dengan studi kepustakaan, menganalisis sumber hukum primer, sekunder, dan tersier terkait digitalisasi akta notaris. Analisis kualitatif deskriptif-analitik diterapkan, termasuk interpretasi hukum dan perbandingan internasional. Hasil penelitian diharapkan dapat berkontribusi pada pengembangan kebijakan digitalisasi akta notaris di Indonesia.Digitalisasi akta notaris penting untuk modernisasi sistem notaris di Indonesia, namun terdapat kesenjangan regulasi dalam penataan khusus akta digital. UU Jabatan Notaris belum mengakomodasi akta notaris digital secara eksplisit, sehingga menciptakan ketidakpastian hukum. Tantangan utama termasuk validitas dokumen digital, keamanan data, standarisasi format, dan penyimpanan jangka panjang. Sumber daya manusia perlu dilengkapi dengan keterampilan teknologi, dan kolaborasi antara pemerintah, asosiasi notaris, dan sektor swasta diperlukan untuk berhasil. Digitalisasi menawarkan peningkatan efisiensi, keamanan, dan transparansi dalam praktik notaris. Digitalisasi akta notaris penting untuk modernisasi notaris di Indonesia, meskipun masih ada kesenjangan regulasi, tantangan hukum, dan kebutuhan infrastruktur.